Infância, experiência e ensino de filosofia - Ayany Priscila Pires de Souza (2016)
This thesis aims at working with the concepts of infancy and experience, based on the contemporary philosopher Giorgio Agamben and his work Infancy and History. In addition to this book, in order to explore the ideas extracted from these two concepts, other thinkers who contribute for the articulation between the cited concepts are included. Agamben points, in the book in question, at the contemporary mans incapacity for translating life into experience. Faced with such scarcity, the philosopher thinks existence in a new place, the infancy, stating that it is the original place of human experience. Language also occupies that spot, constituting an original relation. Despite the fact that infancy belongs to a dimension that comes prior to language, it coexists with infancy, resulting in a movement in which language is set as a location for experience to become the truth. The intention is to think and problematize, in the text, the relationship between infancy and experience in the context of Philosophy as a field, thus questioning the mode for teaching it. The motive for this investigation is my experience as a teacher, my discomfort with the practice of Philosophy teaching, as I perceived, a few times, an absence of infancy and experience. The professional masters degree course in Education carries that value of enabling the creation of possible escapes for some teaching practices, because, quite often, the teaching of Philosophy is based on the transmission of the History of Philosophy or the discussion of wellestablished themes. Therefore, students thoughts and inquietudes, their legitimate issues, are left out of the discussion. Curiosity, awe, and the thirst for knowledge, common to infancy (to all infancy), increasingly tend to be suffocated by curricular and institutional demands, along with a conception of the teaching of Philosophy that causes in the student, as well as in the teacher, a poverty of experience and thinking. That is why strategies that surpass what is already common in teaching Philosophy, its history or its known themes become necessary. From the problems generated in the practice, through a conceptual study, the product is elaborated, aiming at encouraging teachers to create possibilities of philosophical experiences in the classroom. The hypothesis defended in this thesis is that the teacher should allow infancy, which is the students authority experience, catching ideas and issues, and letting students, in fact, exercise Philosophy, create ideas, create their own discourses and ways of thinking.